One Health and Global Health View of Antimicrobial Susceptibility through the “Eye” of Aeromonas: Systematic Review and Meta-Analysis - (:unkn) unknown (My University, 2023)
Antimicrobial resistance (AMR) is one of the most pressing public health concerns; therefore, it is imperative to advance our understanding of the factors influencing AMR from Global and One Health perspectives. To address this, Aeromonas populations were identified using 16S rRNA gene libraries among human, agriculture, aquaculture, drinking water, surface water, and wastewater samples, supporting its use as indicator bacteria to study AMR. A systematic review and meta-analysis was then performed from Global and One Health perspectives, including data from 221 articles describing 15 891 isolates from 57 countries. The interconnectedness of different environments was evident as minimal differences were identified between sectors among 21 different antimicrobials. However, resistance to critically important antibiotics (aztreonam and cefepime) was significantly higher among wastewater populations compared with clinical isolates. Additionally, isolates from untreated wastewater typically exhibited increased AMR compared with those from treated wastewater. Furthermore, aquaculture was associated with increased AMR to ciprofloxacin and tetracycline compared with wild-caught seafood. Using the World Health Organization AWaRe classifications, countries with lower consumption of “Access” compared to “Watch” drugs from 2000 to 2015 demonstrated higher AMR levels. The current analysis revealed negative correlations between AMR and anthropogenic factors, such as environmental performance indices and socioeconomic standing. Environmental health and sanitation were two of the environmental factors most strongly correlated with AMR. The current analysis highlights the negative impacts of “Watch” drug overconsumption, anthropogenic activity, absence of wastewater infrastructure, and aquaculture on AMR, thus stressing the need for proper infrastructure and global regulations to combat this growing problem.
Keywords: aquaculture; wastewater; Aeromonas; clinical; antimicrobial resistance; anthropogenic activity; environmental performance